Whoever Comes to Us With a Cyber Sword: Russian and U.S. Approaches to Deterrence in Cyberspace - O. I. Shakirov (Международная аналитика)
Developed in recent decades, the understanding of cyberspace as an environment in which a state can face serious threats to its security has contributed to a search for ways to prevent such threats. In the military and political spheres, the concept of deterrence has become one of the ways to solve this problem. During the Cold war, the policy of deterrence became central to the strategic thought in the leading countries, but the direct transfer of conventional approaches to a new reality turns out to be problematic. On the one hand, this opens up a debate about the ways to attain deterrence in cyberspace via traditional and new mechanisms. However, theoretical discussions on cyberspace deterrence highlight the limitations of this concept. At the same time, despite some uncertainties that stem from such a transfer, in practice, the leading states use the concept of deterrence in the context of their activities related to cyberspace, although they implement it differently. In this regard, the article suggests focusing on states’ interpretation of deterrence when designing and implementing their policies in this area, rather than on the problems of applying the concept of deterrence. Such a constructivist approach allows to reveal the peculiarities of the understanding of deterrence without considering them predetermined and identify common aspects of views. Using Russia and the United States as examples, we studied specific features of the application of the deterrence concept in respect to cyberspace in official documents and in the course of the practical implementation of their provisions. The analysis shows that countries interpret the concept of cyberspace deterrence in diff erent ways, with an emphasis on specific deterrence strategies. At the same time, Russia and the United States influenced each other while developing views on deterrence.